Associations between plasma metal mixture exposure and risk of hypertension: A cross-sectional study among adults in Shenzhen, China - Zheng, Sijia; Nie, Zhiqiang; Lv, Ziquan; Wang, Tian; Wei, Weizhou; Fang, Daokui; Zou, Xuan; Fu, Yulin; Cao, Tingting; Liang, Zhaoyi; Lu, Qi; Huang, Hui; et al. (Frontiers in Public Health, 2022)
Background: Metal exposure affects human health. Current studies mainly focus on the individual health effect of metal exposure on hypertension (HTN), and the results remain controversial. Moreover, the studies assessing overall effect of metal mixtures on hypertension risk are limited. Methods: A cross-sectional study was conducted by recruiting 1546 Chinese adults who attended routine medical check-ups at the Eighth Affiliated Hospital of Sun Yat-sen University, Shenzhen. The plasma levels of 13 metals were measured using inductively coupled plasma mass spectrometry. Multivariate logistic regression model, restricted cubic spline (RCS) model and the Bayesian Kernel Machine Regression (BKMR) model were applied to explore the single and combined effect of metals on the risk of HTN. Results: A total of 642 (41.5%) participants were diagnosed with HTN. In the logistic regression model, the adjusted odds ratios (ORs) were 0.71 (0.52, 0.97) for cobalt, 1.40 (1.04, 1.89) for calcium, 0.66 (0.48, 0.90) and 0.60 (0.43, 0.83) for aluminum in the second and third quartile, respectively. The RCS analysis showed a V-shaped or an inverse V-shaped dose-response relationship between metals (aluminum or calcium, respectively) and the risk of HTN (P for non-linearity was 0.017 or 0.009 respectively). However, no combined effect was found between metal mixture and the risk of hypertension. Conclusions: Plasma levels of cobalt, aluminum and calcium were found to be associated with the risk of HTN. Further studies are needed to confirm our findings and their potential mechanisms with prospective studies and experimental study designs.